Civilian lyrics of A. Darzhay in comparison of Yakut poetry from 1980’s to 2000’s - Dongak, Uran A. (The New Research of Tuva, 2015)
Article presents a comparison analysis of civil lyrics of Tuvan poet Alexander Darzhay and Yakut poetry from 1980’s to 2000’s. It reveals the ideological and aesthetic community and national identity of Tuvan and Yakut poets.